2001
DOI: 10.1006/icar.2001.6640
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Jovian Stratosphere at the Galileo Probe Entry Site

Abstract: The structure of the Jovian stratosphere at the Galileo probe entry site is investigated through calculations of radiative heating rates based on measurements of the temperature profile, composition, and aerosol distribution. From analysis of mid-IR observations of Jupiter, we determine a C 2 H 2 mole fraction of 1.1-4.3 × 10 −6 at 0.01 mbar, and a C 2 H 6 mole fraction of 2.8-6.5 × 10 −6 at 0.4-10 mbar. The derived distributions imply that C 2 H 6 and C 2 H 2 are the most important coolants in the Jovian stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 71 publications
6
56
2
Order By: Relevance
“…At cooler temperatures, TiO and VO condense and rain out, leaving Na and K as the main optical opacity sources, and allowing the radiation to penetrate to greater depths, with a behavior more like that of L dwarfs. Burrows et al (2008) find similar molecular behavior but also allow for absorption of additional hypothetical species, motivated by various tholins and photochemical species discussed in the context of solar system bodies (e.g., West et al 1986;Yelle et al 2001). Depending on where this postulated opacity source is placed, they find a variety of thermal inversions are possible.…”
Section: Discussionmentioning
confidence: 99%
“…At cooler temperatures, TiO and VO condense and rain out, leaving Na and K as the main optical opacity sources, and allowing the radiation to penetrate to greater depths, with a behavior more like that of L dwarfs. Burrows et al (2008) find similar molecular behavior but also allow for absorption of additional hypothetical species, motivated by various tholins and photochemical species discussed in the context of solar system bodies (e.g., West et al 1986;Yelle et al 2001). Depending on where this postulated opacity source is placed, they find a variety of thermal inversions are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Sada et al (1998) measured a mole fraction of acetylene of (1.8 -2.8) ϫ 10 Ϫ8 in the 1-to 40-mbar region while Noll et al (1986) measured a mixing ratio of (0.7-1.3) ϫ 10 Ϫ7 at about 1.5 mbar. Higher altitude measurements, by Yelle et al (2001) and Bézard et al (1997), yielded respectively a mole fraction of (2-3) ϫ 10 Ϫ6 from 0.004 to 0.02 mbar and a mixing ratio of 1 ϫ 10…”
Section: ϫ8mentioning
confidence: 99%
“…This calculation assumes the C 2 H 2 distribution of model D for pressures higher than 20 mbar. At lower pressures, a distribution simultaneously consistent with the 0-to 20-mbar column abundance of model D and with the results from Noll et al (1986), Sada et al (1998), and Yelle et al (2001) is adopted. This calculation also assumes a thermal profile formed from a smoothed Galileo/ASI profile at pressures lower than 0.1 bar (Yelle et al, 2001) and a thermal profile from the SEB for pressures greater than 0.1 bar [derived following the techniques of Griffith et al (1992)].…”
Section: ϫ7mentioning
confidence: 99%
“…Changes in insolation with latitude over a saturnian year cause latitudinal variations of temperature and photochemistry. Saturn's stratosphere is very similar to Jupiter's, where it has recently been shown that C 2 H 2 and C 2 H 6 are the dominant coolants (Yelle et al, 2001). These molecules are photochemical byproducts of methane photolysis, so their abundance versus latitude may be tied to seasonally varying insolation.…”
Section: Introductionmentioning
confidence: 97%